A new ecology : systems perspective - Nielsen, Sren Nors (Elsevier, 2020)
A New Ecology: Systems Perspective, Second Edition, gives an overview of the commonalities of all ecosystems from a variety of properties, including physical openness, ontic openness, directionality, connectivity, a complex dynamic for growth and development, and a complex dynamic response to disturbances. Each chapter details basic and characteristic properties that help the reader understand how they can be applied to explain a wide spectrum of current ecological research and environmental management applications. --